2019
DOI: 10.1021/acsnano.9b03727
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Magnetic Nanostructures: A Theranostic Platform Targeting Lipid Metabolism and Immune Response in Lymphoma

Abstract: B-cell lymphoma cells depend upon cholesterol to maintain pro-proliferation and pro-survival signaling via the B-cell receptor. Targeted cholesterol depletion of lymphoma cells is an attractive therapeutic strategy. We report here high-density lipoprotein mimicking magnetic nanostructures (HDL-MNSs) that can bind to the high-affinity HDL receptor, scavenger receptor type B1 (SR-B1), and interfere with cholesterol flux mechanisms in SR-B1 receptor positive lymphoma cells, causing cellular cholesterol depletion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…In addition, the thermal activation of MNS core under an external radio frequency field can lead to antitumor immune responses by increasing the heat shock proteins' expression to promote the maturity of APCs and realize lymphocyte trafficking. Besides, HDL-MNS with T 2 enhanced ability and specificity toward the SRB1 receptor cause a distinguishable contrast between SR-B1 positive and negative cells, which highlight its capability in molecular imaging (Singh et al, 2019).…”
Section: Directly Target Cancer Cells For Tumor Theranosticsmentioning
confidence: 96%
“…In addition, the thermal activation of MNS core under an external radio frequency field can lead to antitumor immune responses by increasing the heat shock proteins' expression to promote the maturity of APCs and realize lymphocyte trafficking. Besides, HDL-MNS with T 2 enhanced ability and specificity toward the SRB1 receptor cause a distinguishable contrast between SR-B1 positive and negative cells, which highlight its capability in molecular imaging (Singh et al, 2019).…”
Section: Directly Target Cancer Cells For Tumor Theranosticsmentioning
confidence: 96%
“…Indeed, HDL‐mimetic NPs have been evaluated in vitro and in vivo for the treatment of lymphomas with promise. [ 56,57 ] The following subsections will describe how each of the cell‐mimetic strategies have been applied to the treatment of hematologic malignancies in preclinical studies.…”
Section: Biomimetic Strategies and Adaptationsmentioning
confidence: 99%
“…[ 73 ] Moreover, researchers have shown that NPs can be designed to mimic other structures, such HDL, using a minimum number of biological components (as opposed to entire cell membrane wrappings) to facilitate lymphoma targeting and therapy. [ 56,57 ] Such strategies are exciting approaches in this rapidly evolving field. While biomimetic NPs exhibit substantial promise, there are still concerns that remain to be addressed, such as the potential for immunostimulatory reactions that may result from introducing foreign cell‐derived material into the body.…”
Section: Biomimetic Strategies and Adaptationsmentioning
confidence: 99%
“…Surface modification and high contrast properties of iron oxide NPs give easy access to imaging and diagnostics purposes with MRI and CT scans. Application has been observed in initiating immunotherapy simultaneous to activation of heat shock proteins enhancing immune responses (Medina-Reyes et al, 2017;Singh et al, 2019). Radionuclide in medicine is known as radio nanomedicine abd use radiolabeled nuclei constituting a special group of inorganic NPs.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…A sustained and controlled release can be attained effortlessly by using polymeric NPs because the drug release is either via diffusion, swelling, or via bulk erosion in a time-dependent manner. Properly engineered biodegradable nanomaterials have benefits such as maintaining the drug concentration in the desired range for long periods (Singh et al, 2019). The most prominent property of NPs is the capability to resemble multifunctionality and could be beneficial for immunological cancer research.…”
Section: Inorganic/organic Hybrid Nanoparticlesmentioning
confidence: 99%